The Dynamic and Systemic Effect of Asymmetric Information on Stock Returns by Dumitrescu-Hurlin and Generalized Method of Moments (Case of Tehran Stock Exchange) - Saeed Dehghan Khavari; Seyed Hossein Mirjalili; Mohammadhossein Abdorrahimian; Farzad Bahari Moghaddam (International Journal of Finance and Managerial Accounting, 2023)
The ultimate goal of all investments in stock markets is to earn a satisfactory return on investment, but this is difficult to achieve without enough information to predict stock returns. Information asymmetry refers to a situation where some investors have access to private information that is not reflected in the prices and is yet to be revealed to others. Information asymmetry as a market failure can lead to adverse effects such as poor investor decisions, increased corporate investment risk, and finally reduced stock returns. The issue is important in capital market of developing countries particularly due to the incomplete voluntary disclosure of information as well as its low quality and defective regulatory system. Therefore, in this study, the effect of information asymmetry on stock returns has been investigated in a select group of companies listed in Tehran Stock Exchange. The analysis of this relationship was conducted dynamically for the short-term and long-term using Westerlund and Dumitrescu-Hurlin tests and Generalized Method of Moments to achieve articulated results. Using the tests is suitable with cross-sectional dependence of variables and error terms. Also, using the method is appropriate for measuring lagged effect of dependent variable and removing the bias caused by the endogeneity of explanatory variables. The results demonstrate a significant relationship between information asymmetry and stock return dynamically in short- and long run. The results show that there is a negative systemic effect of information asymmetry on stock return. Also, debt to asset, profit to sales, firm size and lagged stock return effects are significant.
Keywords: 330; Stock Return; Information Asymmetry; Tehran Stock Exchange; Panel Data